Preparation and evaluation of poly(l-histidine) based pH-sensitive micelles for intracellular delivery of doxorubicin against MCF-7/ADR cells - Nan Jia; Yuqing Ye; Qi Wang; Xiuli Zhao; Haiyang Hu; Dawei Chen; Mingxi Qiao (Elsevier, 2017)
In this study, a pH-sensitive micelle self-assembled from poly(l-histidine) based triblock copolymers of poly(ethylene glycol)-poly(d,l-lactide)-poly(l-histidine) (mPEG-PLA-PHis) was prepared and used as the intracellular doxorubicin (Dox) delivery for cancer chemotherapy. Dox was loaded into the micelles by thin-film hydration method and a Box-Behnken design for three factors at three levels was used to optimize the preparations. The optimized mPEG-PLA-Phis/Dox micelles exhibited good encapsulation efficiency of 91.12%, a mean diameter of 45 nm and narrow size distribution with polydispersity index of 0.256. In vitro drug release studies demonstrated that Dox was released from the micelles in a pH-dependent manner. Furthermore, the cellular evaluation of Dox loaded micelles displayed that the micelles possessed high antitumor activity in vitro with an IC50 of 35.30 µg/ml against MCF-7/ADR cells. The confocal microscopy and flow cytometry experiments indicated that mPEG-PLA-Phis micelles mediated efficient cytoplasmic delivery of Dox with the aid of poly(l-histidine) mediated endosomal escape. In addition, blank mPEG-PLA-Phis micelles were shown to be nontoxic to MCF-7/ADR cells even at a high concentration of 200 µg/ml. The pH-sensitive mPEG-PLA-PHis micelles have been demonstrated to be a promising nanosystem for the intracellular delivery of Dox for MDR reversal.